The Effect of Income and Consumption on Consumer Behavior: Indonesian - Safira, Vivi; Penus Leonard Roningsih Sinurat; Meutia Fahrani; Deyren Firmansyah; Boy Mangasi Tua Siregar (Outline Journal of Economic Studies, 2024)
This research was conducted in Deli Serdang Regency with the aim of knowing the effect of income and consumption on consumer behavior in Deli Serdang Regency. Family income is the main factor in household consumption behavior. In carrying out consumption activities, this must be in accordance with the Indonesian economy. This study aims to determine the influence of family income on household consumption behavior in accordance with the principles of consumption in Islam. This research is a type of field research. The research sample was taken using a non-probability sampling technique with 50 respondents. Data collection using the questionnaire method the collected data were analyzed using descriptive analysis techniques, classical assumption tests, and simple regression analysis. The results of the study indicate that there is a positive influence between family income and house hold consumption behavior.